The scientific revolution : A brief history with documents - Jacob, Margaret C. (Boston Bedford/ST. Martin's, 2010)
Exploring the Scientific Revolution from its origins in the early sixteenth century to its widespread acceptance in Western societies in the late eighteenth century, Scientific Revolution argues that the revival of ancient texts in the Renaissance and the upheaval of the Protestant Reformation paved the way for science.
Index: p.145-153
Keywords: Sách tham khảo